Сравнительный анализ энергетической эффективности различных способов утилизации теплоты продуктов сгорания в топливных печах - Сорока, Б.С.; Воробьев, Н.В. (Энерготехнологии и ресурсосбережение, 2013)
Сопоставлена энергетическая эффективность топливных печей при использовании систем утилизации теплоты с помощью централизованных рекуператоров (CR) и с помощью горелок — утилизаторов теплоты (ГУТ): рекуперативных RB и регенеративных RegB. Выполнен анализ работы «идеальной» системы «печь — рекуператор (утилизатор теплоты)» при заданных КПД использования топлива hf и теплоты hН в печи для двух способов задания степени утилизации теплоты: в форме температурного критерия e и энтальпийного критерия e*, предложенного нами. Анализ выполнен для степеней (глубин) утилизации теплоты e и e*, соответствующих сравниваемым системам утилизации. Показано, что возможность обеспечения заданных величин КПД hf и hН в «идеальной» системе «печь — утилизатор теплоты» достигается при различных температурах подогрева воздуха горения ta, зависящих от уровня технологических температур печи (температуры уходящих газов tg,ex). По этой причине уровень ta для случаев централизованного и рассредоточенных утилизаторов теплоты является существенно различным. Проведены расчеты необходимых температур подогрева воздуха горения при различной степени утилизации теплоты (e, e*), характерной для сравниваемых типов теплоутилизирующих систем: e, e* (CR), равных 0,4, и e, e* (RB), равных 0,6. Установлено, что для обеспечения равных КПД печей традиционных конструкций с централизованным рекуператором и печей, отапливаемых с помощью ГУТ, последние должны обеспечивать существенно более высокую температуру подогрева воздуха (дополнительный подогрев воздуха ΔTa ≈ 400 K), чем централизованный рекуператор для случая противоточной печи. Порівняно енергетичну ефективність паливних печей при використанні систем утилізації теплоти за допомогою централізованих рекуператорів (CR) та за допомогою пальників — утилізаторів теплоти (ПУТ): рекуперативних RB та регенеративних RegB. Проведено аналіз роботи «ідеальної» системи «піч — рекуператор (утилізатор теплоти)» при заданих ККД використання палива hf та теплоти hH у печі для двох способів завдання ступеня утилізації теплоти: у формі температурного критерію e та ентальпійного критерію e*, запропонованого нами. Аналіз виконано для ступенів (глибин) утилізації теплоти e та e*, що відповідають порівнюваним системам утилізації. Показано, що можливість забезпечення бажаних ККД hf та hН в «ідеальній» системі «піч — утилізатор теплоти» досягається при різних температурах підігріву повітря горіння ta, що залежить від рівня технологічних температур печі (температури вихідних газів tg,ex). З цієї причини рівень ta для випадків централізованого та розосереджених утилізаторів теплоти є суттєво різним. Проведено розрахунки необхідних температур підігріву повітря горіння при різних ступенях утилізації теплоти (e, e*), характерної для порівнюваних типів теплоутилізаційних систем: e, e* (CR), що дорівнює 0,4, та e, e* (RB), що дорівнює 0,6. Встановлено, що для забезпечення однакових ККД печей традиційних конструкцій з централізованим рекуператором та печей, опалювальних за допомогою ГУТ, останні мають забезпечувати істотно вищу температуру підігріву повітря (додатковий підігрів повітря ΔTa ≈ 400 K), ніж централізований рекуператор для випадку протитокової печі. The scientific and engineering fundamentals of heat recovery processes in fuel furnaces have been advanced in the paper under consideration. The modern European state of development the heat recovery equipment for the fuel furnaces is presented from the standpoint of combustion air preheating and of proper conditions. Efficiency of the furnaces equipped with the various types of heat recovery plants is estimated by means of fuel hf and heat hН utilization efficiency for the furnaces of different purpose. The furnaces with central recuperator and joint burner and heat recovery appliances: recuperative burners RB and regenerative burners RegB — are considered. The last two types of facilities repities representing the decentralized heat recovery plants are characterized by greatly enhanced combustion air preheating in comparison with the preheated air temperature in central recuperators. The power efficiencies of fuel furnaces have been compared under application of two various heat recovery systems: by means of centralized recuperators (CR) and the burners — heat recovery facilities (BHRF): RB and RegB. An analysis of operation process of «ideal» system «furnace — recuperator (heat recovery plant)» has been carried out by two methods of assignment the heat recovery degree: in form of temperature criterion e and enthalpy criterion e* — under given efficiencies of fuel hf and heat hН utilization. The last original criterion (e*) has been proposed by authors. The analysis was performed for degree (depth) of heat recovery e (e*) equal to 0.4 and to 0.6 those meet CR and RB heat recovery systems — correspondingly. It has been found that condition of equal values of power efficiency for the traditional furnace design with CR and for the furnace equipped with BHRF is provided if the last design would be supplied with combustion air of highly enhanced preheating temperature (supplementary value of DTa » 400 K) in comparison with centralized recuperator of counter current flow furnace. Contrary to wide — spread opinion, an application of BHRF in the furnaces in itself does not mean a presence of guarantee of the furnace plant’s high power efficiency but only satisfies a condition of attainment the purpose of high power (fuel) efficiency by optimization the complex of «furnace — heat recovery plant».